Failure Mechanism of a Coal-Rock Combined Body with Inclinations of Structural Planes and a Calculation Model for Impact Energy - Yi-Chao Zhao; Ming-Shi Gao; Yong-Liang He; Dong Xu (Advances in Civil Engineering)
A coal-rock (CR) combined body can be used to simulate structures of coal and rock strata, and its impact-induced failure characteristic conforms more close to engineering practice. Exploring the mechanical properties and impact energy in a CR combined body contributes to better predictions of rock bursts in coal mines. In the study, the mechanical properties of CR combined bodies with four different inclinations (0°, 15°, 30°, and 45°) of structural planes were measured, and also their failure mechanism was analysed. Based on the theory of particle mechanics, a calculation model for impact energy in a CR combined body with inclinations was established and then verified by using monitored acoustic emission (AE) data. The test results showed that inclination affected mechanical properties and failure characteristics of the CR combined body, i.e., the larger the inclination, the lower the strength and impact energy in the CR combined body and the lower the level of damage. The proposed calculation model for impact energy revealed the mechanical essence of energy accumulation and release of a CR combined body, providing a reference for investigating rock burst in coal mines.